Sampling of Natural Regeneration - Sahay, B. K. (Indian Forester, 1955)
The assessment of natural regeneration of Sal (Shorea robusta) by sampling has been discussed. A number of sampling patterns under sampling intensities of 10 and 20 per cent have been constructed and the statistic derived have been tested against the actual deviations. A sampling intensity of 20% is indicated for assessing unestablished Sal regeneration in experimental plots of 1 acre. 10% seems to be the optimal sampling intensity for assessing. Recruitment and unestablished Sal regeneration in areas of the order of 2-4 acres. A lesser sampling intensity is indicated for assessing Sal regeneration of the same coefficient of variation in areas up to the order of small sub-compartments.